Investment Management System - Khairul Nizam, Hashim (2002)

(untitled)
Database systems has evolved in the recent years. Nowadays, good decisions require good information that comes from a manageable data store. Data are likely to be managed most efficiently when they are stored in a database. The Internet has transformed database management system and put them moving towards intergrated Internet-enable database applications. These applications help users in performing numerous tasks, including management of user's investment portfolio, which is addressed in this research project. This report discusses the database system development and framework for developing a prototype system for the Investment management System. The system development was designed using the Database Life Cycle (DBLC) approach. Apart from that, this project report also discusses the findings and challenge encountered during the development of the web database system. This prototype system has been successfully developed a presented together with a user manual designed as a guide for the system users. Hopefully, that this prototype system will contribute as a model and used as a reference for full implementation of the Investment Management System.